Development of single phase H-Bridge cascade multilevel 1KW inverter using SHEPWM switching technique - Mohd Hafiz Arshad (School of Electrical Systems Engineering, 2013)
The main objective of this research is to reduce the harmonics and power loss which usually occur in conventional inverters.